SYNTHESIS AND INVESTIGATION OF ELECTROCONDUCTIVE ORGANIC CONJUGATED SYSTEMS, INCLUDING ELECTROACTIVE AND CHROMOPHORE FRAGMENTS. I. ARYLENEVINYLENES - Abashev, G.G.; Bakiev, A.N.; Vasyanin, A.N.; Ignatenko, E.A.; Komissarova, E.A.; Lunegov, I.V.; Selivanova, D.G.; Shklyaeva, E.V. (Perm Federal Research Centre Journal, 2017)
In the process of project (14-03-96003) implementation we obtained and investigated a large set of new conjugated systems of D-π-D’-π-D (1), D-π-A-π-D (2) and D-A-D (3) types, containing electron donor and electron acceptor carbo- and heterocyclic fragments in various combinations. This article presents only those compounds which belong to the second, D-π-A-π-D group. On the basis of monomers, containing polymerizable units, new poly/oligo(arylenevinylens) were obtainedchemically and/or electrochemically. We have studied optical and electrochemical properties of all the prepared compounds; based on the data, obtained as a result of these measurements; the values ofoptelсfrontier orbital energies (HOMO/LUMO) and the band-gap values (Egи Eg) were calculated. Allthe prepared compounds were investigated from the point of view of the possibility to form thin films. The resulted thin films were obtained with the help of different methods, such as electrochemical deposition, spin-coating and free evaporation. The surface structure and morphology of the obtained films were examined with the help of AFM, STM and SEM methods. We have initiated an investigation of the behavior of some prepared in the course of this work polymers in a solution, determination of some of their electro kinetic parameters, particle sizes and their changes in time.